Laboratory assessment of endogenous intoxication in myocardial infarction patients - A. N. Afanasyeva; S. V. Demyanov; A. N. Repin; S. A. Afanasyev; V. A. Markov; V. A. Evtushenko (Российский кардиологический журнал)
The aim of the study was to investigate the dynamics of main endogenous intoxication (EI) parameters in the first 14 days of myocardial infarction (MI), as well as to study their role in MI severity assessment. In total, 56 patients with acute Q-wave MI, hospitalized in the first 24 hours, were examined: 41 individuals without cardiogenic shock (CS), 15 patients with CS symptoms at admission. Among 15 CS patients, 12 died from progressing left ventricular failure on Days 1-2. Blood levels of creatine phosphokinase (KK), total and effective albumin (ТА, ЕА), middle-mass molecules (МММ), white blood cells (WBC), and WBS subpopulations were measured. On this basis, albumin binding reserve (ABR), toxicity index (TI), intoxication coefficient (1С), WBC intoxication index (WBC II) were calculated. Increased toxemia levels were observed through the whole study period. WBC, WBC II, KK levels peaked in the first 1-2 days of MI. TI and МММ levels were constantly increased (for at least 2 weeks), corresponding to clinical status severity. Blood Albumin and toxemia measurement facilitates rapid (in the first few post-admission minutes) assessment of clinical status severity in MI patients, therefore assisting in identifying individuals who need intensive monitoring and aggressive treatment.